Feasibility of Manufacturing Dielectric Image Lines by Using Laser-Based Directed Energy Deposition of Polymers - Wittmann, Alexander; Bader, Tobias; Alidoust Chamandani, Saeed; Hentschel, Oliver; Schmidt, Michael; Gold, Gerald (IEEE Access, 2023)
The laser-based directed energy deposition of polymers (DED-LB/P) is an additive manufacturing process which offers the possibility to build up 3D structures with a high level of individualization on free-form surfaces. In this article, an absorber free DED-LB/P process with a thulium-doped fiber laser is presented for the first time to produce dielectric image lines (DIL) consisting of polypropylene (PP) for high frequency applications. This type of transmission line has advantages over the commonly used stripline technology due to its low signal attenuation, especially at high frequencies, but is currently hardly found in mass-market applications because no suitable manufacturing technology has been established for it yet. The steadily increasing demand of higher bandwidth in telecommunication or increased resolution of radar sensors leads to higher application frequencies and alternative interconnect technologies will become more important as they significantly define the achievable overall system performance. Based on the fabricated low-loss DILs in this study, DED-LB/P could represent such an alternative manufacturing process for future RF-applications.<br
Keywords: additive manufacturing; dielectric image lines; directed energy deposition; laser polymer deposition